Left Ventricular Noncompaction Syndrome: A Rare Congenital Cardiomyopathy - Ashwini V. Mallad; Waseem Ahmed; Madhulika Urella; Mehiar El-Hamdani (Marshall Journal of Medicine, 2016)
Isolated left ventricular noncompaction cardiomyopathy (LVNC) is a rare congenital condition occurring due to arrest of myocardial compaction in the first trimester, resulting in a thin layer of compacted epicardium and thick hypertrabeculated myocardium containing deep recesses. This article presents a 44-year-old female with progressive dyspnea, orthopnea, paroxysmal nocturnal dyspnea, and pleuritic chest pain. Examination revealed elevated jugular venous distention, lower extremity edema, and bibasilar crackles on lung auscultation, while the electrocardiogram (EKG) exhibited left bundle branch block. Two-dimensional echocardiography (2D-Echo) showed a dilated left ventricle (LV) with ejection fraction (EF) of 25% and severe diffuse hypokinesia. Cardiac magnetic resonance imaging (MRI) confirmed the diagnosis of LVNC. Thereafter, she developed atrial fibrillation with rapid ventricular rate. Conservative treatment was initiated with Tikosyn, Xarelto, Lasix, Toprol XL, Lisinopril, statin and life vest. Eventually, a cardiac resynchronization therapy defibrillator (CRT-D) was implanted to prevent sudden cardiac death and reduce heart failure complications.